Prescription drug monitoring programs, nonmedical use of prescription drugs, and heroin use: Evidence from the National Survey of Drug Use and Health. (June 2017) - Ali, Mir M.; Dowd, William N.; Classen, Timothy; Mutter, Ryan; Novak, Scott P.
Abstract: In the United States, nonmedical prescription opioid use is a major public health concern. Various policy initiatives have been undertaken to tackle this crisis, including state prescription drug monitoring programs (PDMPs). This study uses the 2004–2014 National Survey of Drug Use and Health (NSDUH) and exploits state-level variation in the timing of PDMP implementation and PDMP characteristics to investigate whether PDMPs are associated with a reduction in prescription opioid misuse or whether they have the unintended consequence of increasing heroin use. In addition, the study examines the impact of PDMPs on the availability of opioids from various sources. The study finds no effect of PDMP status on various measures of nonmedical prescription opioid use (abuse, dependence, and initiation), but finds evidence of a reduction in the number of days of opioid misuse in the past year. The study also finds that implementation of PDMP was not associated with an increase in heroin use or initiation, but was associated with an increase in number of days of heroin use in the past year. Findings also suggest that PDMPs were associated with a significant decline in doctor shopping among individuals without increasing reliance on illegal sources (e.g., drug dealers, stealing, etc.) or social sources (friends or relatives) as a means of obtaining opioids. The President's FY2017 budget proposed the allocation of 1.1 billion in an effort to reduce prescription drug misuse, and highlighted the use of PDMPs as a policy tool. This study documents evidence that PDMPs might be having measurable impact. Highlights: First paper to examine the role of prescription drug monitoring program (PDMP) on individual level opioid related outcomes. Significant association between PDMP implementation and reduction in 'doctor shopping' behavior. No significant associations between PDMP implementation or its associated features on heroin initiation. No significant associations between PDMP implementation on nonmedical use/initiation/abuse of opioids.